The Effect of Liquidity, Leverage, Good Corporate Governance, and Firm Size on the Profitability of Maritime Transportation Companies Listed in Indonesia - Mila Apriani; Solihin Sidik (Darul Yasin Al Sys, 2026)
Although the maritime transport sector plays a strategic role in Indonesia’s economy, empirical research examining the determinants of shipping profitability amid recent regulatory and market shifts remains limited. This study aims to analyze and empirically test the effects of liquidity, proxied by the Current Ratio; leverage, proxied by the Debt-to-Equity Ratio; Good Corporate Governance, proxied by the proportion of independent commissioners; and firm size on the financial performance of maritime transport issuers listed on the Indonesia Stock Exchange during the 2020–2024 period, measured by Return on Assets. A quantitative approach with a causal-associative design was employed. The sample was selected through purposive sampling, resulting in 11 shipping companies and 55 balanced panel observations. Data were obtained from audited annual financial reports and analyzed using panel data regression with the Fixed Effect Model (FEM) in EViews. The findings indicate that liquidity has a positive and significant effect on Return on Assets, whereas leverage has a significant negative effect. Conversely, Good Corporate Governance and firm size do not have significant effects on profitability. These findings suggest that financial performance in the capital-intensive maritime transport sector is primarily determined by working capital efficiency and debt control rather than board composition or scale expansion. This study contributes to the development of agency theory and signaling theory by demonstrating context-specific resource constraints in emerging maritime markets. The findings provide practical implications for shipping management, creditors, and regulators by emphasizing the importance of rigorous short-term liquidity management and optimal leverage thresholds to sustain long-term maritime financial performance.